Surface Functionalization of Cotton Fabrics by Photo-Grafting for pH Sensing Applications - Kianfar, Parnian; Abate, Molla Tadesse; Trovato, Valentina; Rosace, Giuseppe; Ferri, Ada; Bongiovanni, Roberta; Vitale, Alessandra (Frontiers in Materials, 2020)
This paper investigates the photo-grafting of a halochromic molecule on cotton fabric surfaces. nitrazine yellow (NY) dye was modified with a methacrylate moiety (GMA) obtaining a photo-reactive dye (GMA-NY), which was covalently grafted onto the cellulosic substrate by means of UV irradiation. The photo-grafting reaction was studied by FT-IR spectroscopy, while the pH response of the functionalized fabric was evaluated at different pH conditions (i.e., acidic and alkaline conditions) both in wet and vapor environments by spectrophotometric analyses. The results showed that the photo-grafting of the modified dye onto the fabric was successful: treated cotton clearly changed color when subjected to different pH. It was thus demonstrated that the GMA-NY dye, photo-grafted on cotton, can successfully impart pH sensing properties to the fabric, which can therefore find numerous applications in the area of smart textiles.